Coronal Shear Fractures of the Distal Humerus - Enrico Bellato; Riccardo Giai Via; Daniel Bachman; Ilaria Zorzolo; Antonio Marmotti; Filippo Castoldi (Journal of Functional Morphology and Kinesiology, 2022)
Coronal shear fractures of the distal humerus are rare, frequently comminuted, and are without consensus for treatment. The aim of this paper is to review the current concepts on the diagnosis, classification, treatment options, surgical approaches, and complications of capitellar and trochlear fractures. Computed Tomography (CT) scans, along with the Dubberley classification, are extremely helpful in the decision-making process. Most of the fractures necessitate open reduction and internal fixation, although elbow arthroplasty is an option for comminuted fractures in the elderly low-demand patient. Stiffness is the most common complication after fixation, although reoperation is infrequent.